MATURITY STAGES OF INDIAN OIL-SARDINE, SARDINELLA LONGICEPS VAL., WITH NOTES ON INOiDElJCE OF ATRETIC FOLLICLES IN ADVANCED OVARIES - Raja, B T Antony (Indian Journal of Fisheries, 2011)
WORKERS engaged in research on the maturity and spawning conditionsoffish have prepared different types of maturity scale according to the peculiaritiespresented by different fishes studied by them. Except for a fewremarks about the external appearance of ovaries belonging to stages V toVII by Devanesan (1942), there is no detailed account of the different stagesof maturity for Sardinella longiceps. Nair (1959) has adopted the maturityscale prepared by the International Coij^cil for the Exploration of the Seafor investigations on oil-sardine. However, when studies on the maturityand spawning habits of oil-sardine were taken up by the author, the absenceof a detailed classification was keenly felt and since the International keywas found to be not adequate enough to distinguish the different stages,it was considered necessary to prepare a detailed scale for the guidance ofworkers both in the laboratory and the field so that confusion in the interpretationand assignment of the stages of maturity can be avoided and auniformity in . eporting achieved